Transition metal chemistry - M Gerloch (VCH, 1994)
this book presents the structure of transition metal chemistry. It provides a most accessible text on the varied nature of the valence shell in d-block chemistry, including the stability and reactivity of transition metals in their various oxidation states; spectroscopic and magnetic properties and their implications for chemical bonding in the transition metal series; the changing role of d electrons with respect to oxidation state